Jumpstart RTI using RTI in your elementary school right now - Hall, Susan L. (Susan Long); Sage eBooks (Thousand Oaks, Calif. : Corwin, 2011)
Susan L. Hall asserts that an educator's job is not done until a school's RTI practices result in at least 95 percent of its students reading at benchmark levels. This book's research-based strategies will get you started on the road to achieving those results quickly, efficiently, and successfully. Included are case studies, delivery models, practical tools, reproducibles, analysis worksheets, and forms that can be downloaded from a secure website.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Reading (Elementary) -- United States; Learning disabled children -- Education -- United States; Reading -- Remedial teaching -- United States; Response to intervention (Learning disabled children); Electronic books